Explaining Trends and Factors Affecting Export Diversification in ASEAN and SAARC Regions: An Empirical Analysis - SHABANA NOUREEN; ZAFAR MAHMOOD (NUST Journal of Social Sciences and Humanities)
This paper examines the role played by country-specific factors in the determination of export product diversification process. To meet this objective, the paper begins by constructing a time series data for export diversification using the Herfindahl index. Then, it applies the fully modified OLS co-integration model to a panel of selected ASEAN and SAARC countries to find out the main determinants of export product diversification. Export diversification pattern shows that since the mid-1980s the ASEAN countries have continuously witnessed export diversification and the SAARC countries embarked on export diversification journey since the early 1990s. Analysis of the determinants suggests that foreign direct investment, domestic investment, competitiveness, real depreciation of domestic currency, financial sector development and institutional strength are significantly and positively related to export product diversification in both regions. These findings have important policy implications for the two regions. They call upon the policymakers for further diversification of exports, especially in the areas of their specialization that are vital for their smooth and sustained foreign exchange earnings as well as economic development. The study also recommends improving international competitive strength via improving business environment to achieve the goal of export product diversification.